2012
DOI: 10.1242/jcs.089466
|View full text |Cite
|
Sign up to set email alerts
|

Tiam1-regulated osteopontin in senescent fibroblasts contributes to the migration and invasion of associated epithelial cells

Abstract: SummaryThe tumor microenvironment undergoes changes concurrent with neoplastic progression. Cancer incidence increases with aging and is associated with tissue accumulation of senescent cells. Senescent fibroblasts are thought to contribute to tumor development in aging tissues. We have shown that fibroblasts deficient in the Rac exchange factor Tiam1 promote invasion and metastasis of associated epithelial tumor cells. Here, we use a three-dimensional culture model of cellular invasiveness to outline several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
2
38
1
Order By: Relevance
“…Cancer incidence increases with aging and is associated with tissue accumulation of senescent cells. Liu and colleagues have elegantly shown that senescent fibroblasts promote neoplastic progression in associated tumors through degradation of fibroblast Tiam1 protein and the consequent increase in secretion of OPN by fibroblasts (Liu et al, 2012). …”
Section: Opn Impacts Pathophysiologies Of Multiple Malignanciesmentioning
confidence: 99%
“…Cancer incidence increases with aging and is associated with tissue accumulation of senescent cells. Liu and colleagues have elegantly shown that senescent fibroblasts promote neoplastic progression in associated tumors through degradation of fibroblast Tiam1 protein and the consequent increase in secretion of OPN by fibroblasts (Liu et al, 2012). …”
Section: Opn Impacts Pathophysiologies Of Multiple Malignanciesmentioning
confidence: 99%
“…Three-dimensional co-culture model systems have proven very useful in studying invasion of epithelial cells and epithelial tubes into mesenchymal cell-containing matrices. [35][36][37] In vitro multicellular systems have been useful for studying cell assembly during epithelial cyst formation or branching morphogenesis. 38,39 To model alveolar morphogenesis, we tested multiple 3-D epithelial-mesenchymal co-culture approaches using various matrix compositions, including collagen gels, matrigel, and synthetic hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of osteopontin expression are correlated with this activated phenotype [43]. Increased levels of osteopontin secreted by senescent fibroblasts also promote migration of mammary epithelial cells, a process linked to neoplastic progression and tumor development in aging tissues [44]. Thus osteopontin is predicted to be a primary determinant of the activated phenotype characteristic of adventitial fibroblasts in hypertensive lungs.…”
Section: Osteopontinmentioning
confidence: 99%